2006
DOI: 10.1016/j.virol.2005.10.040
|View full text |Cite
|
Sign up to set email alerts
|

p6gag of human and simian immunodeficiency viruses is tolerant to small in-frame deletions downstream of the late domain

Abstract: Short, unique, in-frame deletions were consistently detected within p6gag sequences obtained over time from three of eight HIV-1-infected long-term nonprogressors (Alexander, L., Weiskopf, E., Greenough, T.C., Gaddis, N.C., Auerbach, M.R., Malim, M.H., O'Brien, S.J., Walker, B.D., Sullivan, J.L., Desrosiers, R.C., 2000. Unusual polymorphisms in Human Immunodeficiency Virus Type 1 associated with nonprogressive infection. J. Virol. 74, 4361-4376). Using PCR mutagenesis, we created 11 mutant forms of SIV239 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…While the PTAP motif is critical for the late stage of viral assembly and mutations introduced to alter this motif may lead to accumulation of virus particles on the plasma membrane, 14,15 the LXXLF motif is participating in the virus budding through interaction with the cellular factor, AIP1/ALIX. 37 Although controversial results were reported in subsequent studies, 17,18 the influences of deletion between P30-Y36 of p6 gag , as observed in CRF07_BC in Taiwan, were not addressed in any of these studies. In the present study, we demonstrated that the naturally occurring 7-amino acid deletion in the p6 of CRF07_BC correlated with reduced Pr55 gag /Pr160 Gag-Pol processing, tethering of virus particles on plasma membrane and reduced incorporation of Vpr in virus particles, which could contribute to reduced replication of CRF07_BC viruses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While the PTAP motif is critical for the late stage of viral assembly and mutations introduced to alter this motif may lead to accumulation of virus particles on the plasma membrane, 14,15 the LXXLF motif is participating in the virus budding through interaction with the cellular factor, AIP1/ALIX. 37 Although controversial results were reported in subsequent studies, 17,18 the influences of deletion between P30-Y36 of p6 gag , as observed in CRF07_BC in Taiwan, were not addressed in any of these studies. In the present study, we demonstrated that the naturally occurring 7-amino acid deletion in the p6 of CRF07_BC correlated with reduced Pr55 gag /Pr160 Gag-Pol processing, tethering of virus particles on plasma membrane and reduced incorporation of Vpr in virus particles, which could contribute to reduced replication of CRF07_BC viruses.…”
Section: Discussionmentioning
confidence: 94%
“…16 These short deletions are all located between the PTAP and LXXLF motifs of p6 gag . Although subsequent studies, using sequential short deletion mutants between E13 and T21 of p6 gag , as well as a long fragment deletion mutant (S14–I31 of p6 gag ), suggested that these mutations had relatively tolerable effects on Gag processing and in vitro viral infectivity, 17,18 the influences of deletion between P30–Y36 of p6 gag , as observed in CRF07_BC in Taiwan, were not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Strack and colleagues initially reported that ALIX binds core sequences of 35 LYPLTSL 41 and 22 LYPDL 26 within the late domains of human immunodeficiency virus type 1 (HIV-1) p6…”
mentioning
confidence: 99%
“…Gag has been analyzed by deletion analysis (26), but unfortunately the functional importance of the key tyrosine residue in the ALIX-binding site was not tested. We therefore used a SIV mac251 -based system (21), for which a vector was available, to test whether noncanonical ALIX-binding sites within SIV p6…”
mentioning
confidence: 99%
“…In those studies that did include in vitro assessments of viral fitness, many of the observed viral sequence polymorphisms did not significantly affect viral infectivity or replication kinetics. 3,20 In the context of a highly heterogeneous virus such as HIV-1, the extent to which observed viral sequence variants cause a substantial decrease in viral fitness and pathogenicity is often difficult to assess, and clear cases of viral attenuation are rare.…”
Section: Differential Diagnosismentioning
confidence: 99%